The development of nutrition pictograph design on food labeling using Delphi Technique / Aida Md Saad ... [et al.] - Md Saad, Aida; Maaruf, Siti Zuraida (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
Recently consumers are facing the issue of health problems such as Non -Communicable Disease (NCD) occurring in the society due to unhealthy lifestyle and behaviours. Consumers have claimed that they have knowledge about nutrition information but with low awareness level to read the nutrition information and difficulties to interpret the nutrition information on the food label. The nutrition contained in the food has been presented in numerical data and unattractive design. Plus, the rush when shopping will make the consumers neglect to read the food label. This research attempted to focus on the development of a suitable and usable nutrition pictograph design as a tool to educate the consumers in choosing a healthier selection of packed food. The researchers used the Delphi Technique as a medium in choosing the appropriate nutrition pictograph design, which should be incorporated into the selected food label. Findings from this study revealed positive feedback and reached a consensus, and all expert panels have agreed on the development of the nutrition pictogram design. Therefore, the implication of this study is targeted towards the consumers, Ministry of Health and food manufacturers. It can also contribute to the growth of the Visual Communication field. This nutrition pictograph design is intended to educate and inculcate the consumers and enhance health awareness in selecting the healthier choice of food.